The Long-Term Effect of Blanket Phosphorus Fertilizer Application on the Available P Content in Sawah Soils; Comparative Study in Java, Indonesia - Darmawan, .; Kyuma, Kazutake; Masunaga, Tsugiyuki; Asmar, .; Darfis, Irwan; Wakatsuki, Toshiyuki (UNIVERSITY OF LAMPUNG, 2009)
In order to evaluate the effects of long-term phosphorus fertilizer application on the sawah soils, a comparative study was conducted in Java Island as a pioneer of Green Revolution (GR) technology application in Indonesia. Soil samples taken in 1970 by Kawaguchi and Kyuma were compared with new sample taken from the same site or the sites close to 1970 in 2003. The results showed that available phosphorus (P) sharply increased during the study period. The average content of available P in topsoil layer changed from 10.5±11.6 mg kg-1 P in 1970 to 19.6±22.4 mg kg-1 P in 2003, or increased by 118%. Long-term application of 125 kg super-phosphate [Ca(H2PO4)2] per hectares per cropping season as P fertilizers was also affected the profile distribution of available P in whole sites studied, especially in Vertisols. The land management differences between seedfarms planted with rice in monoculture systems whole study period and non-seedfarms cultivated rice and upland crops in some rotation patterns found affected the changing rate of available P in the soils. During the period of 1970-2003, average content of available P in seedfarms changed from 15.7±16.2 mg kg-1 P to 31.1±29.1 mg kg-1 P, while in non-seedfarm from 6.9±8.7 mg kg-1 P to 11.5±8.2 mg kg-1 P in 1970 and 2003, respectively. The great variation on the changing rate of available P observed in this study indicated that general chemical fertilizers recommendation in Indonesia was caused excess P input in some sites, but insufficient in others. To avoid the adverse effect of P fertilizer application in the future, recommendation of P should be based on the site characteristic and taking into account of natural resources contribution.